Mengoptimalkan pemanfaatan perpustakaan kampus dalam proses belajar - Auliaa, Amatullah Al (Maliki Interdisciplinary Journal, 2024)
University libraries or campus libraries have an important role as a means of learning resources for students to support the learning process.However, in the last few years the level of campus library utilisation has tended to decline, one of the causes is due to the lack of student awareness of the use of campus libraries as an effective learning resource.To optimise the use of campus libraries, several strategies are needed to attract students such as the existence of complete facilities, a collection of books that are relevant to the needs of students and education about campus libraries so that students have the awareness to make libraries a means of learning resources.Optimal utilisation of campus libraries can help students in obtaining more complete and accurate information.